Comparison of Bupivacaine 0.5% and Bupivacaine + Clonidine Intrathecally for intraoperative and Postoperative analgesia in Lower Limb Orthopaedic Surgeries - Shende, Seema; Bhargava, Sumit; Chakravarty, Nupur; Patel, R P; Prafulla Dave, Sanjay (International Journal of Medical Research and Review, 2014)
Background: A randomized controlled study was designed to investigate the effects of addition of clonidine to hyperbaric bupivacaine 0.5% for spinal anaesthesia in patients undergoing lower limb orthopaedic surgeries, in terms of vital parameters, onset and duration of sensory and motor block, intra and post operative pain and adverse effects. Methods: Sixty adult ASA Grade I and II patients of either sex posted for lower limb orthopedic surgeries were randomly divided equally in to clonidine or control group. Control group received intrathecal 3.0 ml of 0.5% hyperbaric bupivacaine with 0.5 ml of normal saline and Clonidine group received identical volume of intrathecal clonidine with hyperbaric bupivacaine. Results: Mean time for post operative analgesia was significantly longer in clonidine group (9.6 hours) than in the control group (3.55 hours). (p-value<0.01). Heart rate and blood pressure compared at 30 minute and 45 minute intervals were significantly less in clonidine group. ( p-value < 0.05). Bradycardia and hypotension did not require any therapeutic intervention. Clonidine group patients were found to be more sedated than control group. Conclusion: Adding clonidine 75 μg to intrathecal bupivacaine prolongs the duration of spinal anaesthesia and analgesia. It is safe and is likely to be as effective as higher doses of bupivacaine without severe adverse effects.